Good Citizen Interrupted: Calibrating a Temporal Theory of Citizenship Behavior - Methot, Jessica R.; Lepak, David; Shipp, Abbie J.; Boswell, Wendy R. (Academy of Management Review, 2017)
Burgeoning theory and research signal the prominence of within-individual dynamics in organizational citizenship behavior (OCB), with such work focusing primarily on short-term (i.e., minutes, days, weeks) fluctuations that result from a focus on immediate circumstances. But longer-term variations in OCB also occur as people continuously craft identity narratives to tell evolving stories about themselves using selective appropriation of the past, present, and future. By focusing on individuals who have internalized a “good citizen identity” (a reflection of one’s self-concept as a person who demonstrates OCB), we shift attention by presenting theory that speaks to modifications of OCB trends over the course of good citizens’ tenure. We ground our framework in the time-dependent perspectives of sensemaking and dynamic behavior to specify precise temporal relationships between triggering cues and OCB modifications. Specifically, we define a baseline OCB trend and then develop propositions about how sensemaking cues linked to role transitions and work episodes can prompt differences in four trend effects: lag, rate of change, magnitude, and permanence. In doing so we identify circumstances that interrupt good citizens’ ongoing flow and that could spark permanent modifications to OCB.